Addressing contact tracing challenges—critical to halting Ebola virus disease transmission. (December 2015) - Greiner, Ashley L.; Angelo, Kristina M.; McCollum, Andrea M.; Mirkovic, Kelsey; Arthur, Ray; Angulo, Frederick J.
Highlights: The Ebola virus disease outbreak in West Africa is the largest in history. The Ebola virus disease outbreak is the first in West Africa. Timely and effective contact tracing is essential to halting transmission. Challenges are evident in every aspect of the contact tracing process. Addressing contact tracing challenges is critical to halting disease transmission. Summary: Background: Delayed and ineffective contact tracing contributed to the extensive transmission of Ebola virus disease (EVD) in the 2014–2015 West African outbreak. Understanding and addressing the challenges to implementing and managing contact tracing is essential to stopping EVD transmission and preventing large-scale EVD outbreaks in the future. Methods: Interviews were conducted with United States Centers for Disease Control and Prevention staff members engaged in contact tracing activities in the affected West African countries of Sierra Leone, Guinea, Liberia, Senegal, Nigeria, and Mali from September through December 2014. Two staff members from each country were interviewed. The five most frequently cited contact tracing challenges were identified. Results: Challenges have been evident in every step of the contact tracing process from implementation to management, including identifying, locating, and enrolling contact-persons, as well as managing personnel and ensuring contact tracing performance. Common themes observed in all of the affected West African countries have included fear, stigma, and community misperceptions regarding EVD. Countries that have overcome these challenges, ensuring immediate and comprehensive contact tracing, have been successful in halting EVD transmission. Conclusions: Addressing challenges to contact tracing implementation and management in the West African EVD outbreak is essential to stopping ongoing transmission.